IMPROVED CURABLE FIBERGLASS BINDER COMPRISING A ß- AMINO-ESTER OR ß-AMINO-AMIDE CONJUGATE ADDITION PRODUCT - FISLER, DIANA, KIM; SHOOSHTARI, KIARASH, ALAVI (2007)
A curable formaldehyde-free binding composition for use with fiberglass is provided. Such curable composition comprises a conjugate addition product of an amine and an unsaturated reactant in the form of a ß-amino-ester or ß-amino-amide intermediate. The composition when coated on fiberglass is cured to form a water-insoluble polyamide or polyimide binder which exhibits good adhesion to glass. In a preferred embodiment the fiberglass is in the form of building insulation. In other embodiments the product is a microglass-based substrate for use in a printed circuit board, battery separator, filter stock, or reinforcement scrim. L'invention concerne une composition de liaison sans formaldéhyde durcissable utilisable avec de la fibre de verre. Une telle composition durcissable comprend un produit d'addition conjugué d'une amine et un réactif insaturé sous la forme d'un intermédiaire ß-amino-ester ou ß-amino-amide. Recouvrant la fibre de verre, ladite composition est durcie et forme un liant polyamide ou polyimide insoluble dans l'eau qui présente une excellente adhérence au verre. Dans un mode de réalisation, la fibre de verre se présente sous forme d'isolants de bâtiments. Dans d'autres modes de réalisation, le produit est un substrat à base de microverre utilisable en tant que carte imprimée, séparateur de piles, matériau filtrant, ou renforts tissés.